Reflection on Partisan War and Images of the Enemy in the Publication Prie rymančio Rūpintojėlio (1949–1953) - Paskočiumaitė-Petruškevičienė, Greta (Tautosakos darbai, 2025)
The article analyzes the content of the periodical of the Lithuanian Freedom Fight Movement, Prie rymančio Rūpintojėlio (1949–1953). The periodical is perceived as an instrument that formed the collective identity of the partisans and represented an ideologically tinted narrative of the partisan war, designed to strengthen the determination of the fighters to resist and provide a contrast to the myths spread by the Soviet propaganda. Based on the documents of the partisan leadership, it can be stated that the newspaper was regarded as exemplary for all the partisan units, conveying the leadership’s attitude to the struggle and shaping the images of the partisans and their enemies. The title of the publication [‘By the pensive Christ’] suggests the activities of the partisans being inseparable from the Christian values. Attention is also paid to determination, the importance of public support, and fearlessness, which highlight the idealized image of the fighter. Although some of the leadership criticized the image of the pensive Christ as the main symbol and suggested that more emphasis be placed on images that encouraged fighting, the content of the publication remained largely consistent throughout the entire period of publication. The role of the partisans as fighters representing goodness and spiritual values was reinforced by images of the enemy: both external and internal enemies were depicted as morally wrong and not to be feared by the partisans. All this corresponded to the partisan leadership’s concept of the fight and allowed for enhancing its meaning.